Endoscopic submucosal dissection of early gastric cancer via inverted overtube in a patient with situs inversus totalis: a case report - Miyaoka, Youichi; Suemitsu, Shinsuke; Fujiwara, Aya; Kotani, Satoshi; Tsukano, Kosuke; Yamanouchi, Satoshi; Kusunoki, Ryusaku; Miyake, Tatsuya; Fujishiro, Hirofumi; Kohge, Naruaki; Yamamoto, Tomohiko; Amano, Yuji (Endoscopy International Open, 2018)
Background and study aims A 72-year-old man with complete situs inversus presented with early gastric cancer on the lesser curvature wall of the antrum of the stomach. Endoscopic submucosal dissection (ESD) was selected as a treatment. When the patient was positioned in the left decubitus position, the lesion was hidden by blood and gastric fluid because it was located on the gravitational side. Therefore, we decided to perform ESD with the patient in the right lateral decubitus position and use an inverted overtube, which provided a good endoscopic view without the need to rearrange the endoscopist, assistants, or endoscopic system. ESD was safe and feasible using the inverted overtube.